Manipulations of Oblique Pulling Affect Sacroiliac Joint Displacements and Ligament Strains: A Finite Element Analysis. (3rd January 2023) - Xu, Zhun; Feng, Ziyu; Zhang, Zhaocong; Zhang, Kunmu; Li, Yikai
Abstract : Objective. Clinical studies have found that manipulation of oblique pulling has a good clinical effect on sacroiliac joint pain. However, there is no uniform standard for manipulation of oblique pulling at present. The purpose of this study was to investigate the effects of four manipulations of oblique pulling on sacroiliac joint and surrounding ligaments. Methods. A three-dimensional finite element model of the pelvis was established. Four manipulations of oblique pulling were simulated. The stresses and displacements of sacroiliac joint and the strains of surrounding ligaments were analyzed under four manipulations of oblique pulling. Results. Manipulation of oblique pulling F2 and F3 caused the highest and lowest stress on the pelvis, at 85.0 and 52.6 MPa, respectively. Manipulation of oblique pulling F3 and F1 produced the highest and lowest stress on the left sacroiliac joint, at 6.6 and 5.6 MPa, respectively. The four manipulations of oblique pulling mainly produced anterior-posterior displacement. The maximum value was 1.21 mm, produced by manipulation of oblique pulling F2, while the minimal value was 0.96 mm, produced by manipulation of oblique pulling F3. The four manipulations of oblique pulling could all cause different degrees of ligament strain, and manipulation of oblique pulling F2 produced the greatest ligament strain. Conclusions. The four manipulations of oblique pulling all produced small displacements of sacroiliac joint. However, they produced different degrees of ligament strain. Manipulation of oblique pulling F2 produced the largest displacement of sacroiliac joint and the greatest ligament strain, which could provide a certain reference for physiotherapists.